2020
DOI: 10.1002/ags3.12377
|View full text |Cite
|
Sign up to set email alerts
|

Viral elimination is essential for improving surgical outcomes of hepatitis C virus‐related hepatocellular carcinoma: Multicenter retrospective analysis

Abstract: Aim The impact of sustained virologic response (SVR) on surgical outcomes for patients with hepatitis C virus (HCV)‐related hepatocellular carcinoma (HCC) remains controversial. This study aimed to evaluate the influence of SVR on long‐term surgical outcomes after hepatectomy. Methods This multicenter study included 504 patients who underwent curative resection for HCV‐related HCC. Patients with a history of HCC treatment, HBV infection, poor liver function, and tumor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In our study, lower levels of liver enzymes, a higher proportion of ALBI grade I, higher platelet counts, and a numerically lower incidence of liver cirrhosis in patients achieving SVR before HCC diagnosis indicated that HCV clearance improved hepatitis, leading to a lower degree of liver fibrosis and incidence of cirrhosis as well as a better liver function. These findings were consistent with the results of prior studies [24][25][26][27]. Notably, as many as 75.6% of patients who developed HCC after achieving SVR did not have cirrhosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, lower levels of liver enzymes, a higher proportion of ALBI grade I, higher platelet counts, and a numerically lower incidence of liver cirrhosis in patients achieving SVR before HCC diagnosis indicated that HCV clearance improved hepatitis, leading to a lower degree of liver fibrosis and incidence of cirrhosis as well as a better liver function. These findings were consistent with the results of prior studies [24][25][26][27]. Notably, as many as 75.6% of patients who developed HCC after achieving SVR did not have cirrhosis.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, patients with persistent viremia had worse surgical outcomes. One multicenter study including 504 Japanese patients who had HCV-related HCC and underwent curative resection exhibited significantly better survival outcomes in patients achieving SVR either before or after hepatectomy than those without SVR [27]. Another study from Japan showed that achieving SVR before HCC development allowed a superior clinical outcome after curative ablation in HCV-related HCC patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…Today HCV can be eliminated in almost all cases, and it is necessary to clarify that at least antiviral treatment has not worsened the surgical outcomes of HCC. Therefore, in a multicenter study, we investigated the impact of SVR before and after hepatectomy on the long-term surgical outcomes of HCV-related HCC after statistically minimizing bias arising from patients' background characteristics [77]. Two hundred ninety-six patients underwent radical hepatectomy for primary HCV related HCC, of which 58 achieved SVR before hepatectomy (Pre-SVR group), 54 achieved SVR after hepatectomy, and 186 without achieving SVR (Non-SVR group).…”
Section: The Impact Of Hcv Eradication On Surgical Outcomes For Hccmentioning
confidence: 99%
“…Liver resection is one of the most favorable treatments for HCC, but the recurrence rate after surgery is 70%, which is extremely high 2,3 . Various adjuvant therapies, including viral elimination, hepatic infusion chemotherapy, systemic chemotherapy, and immunotherapy, have been used to prevent recurrence 4–7 . However, no adjuvant therapy in phase III trials has shown a significant survival benefit for patients with resectable HCC, and the development of effective adjuvant therapies is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Various adjuvant therapies, including viral elimination, hepatic infusion chemotherapy, systemic chemotherapy, and immunotherapy, have been used to prevent recurrence. [4][5][6][7] However, no adjuvant therapy in phase III trials has shown a significant survival benefit for patients with resectable HCC, and the development of effective adjuvant therapies is warranted. By contrast, the effectiveness of the combination therapy of atezolizumab, an immune checkpoint inhibitor (ICI), and bevacizumab, an angiogenesis inhibitor, for the treatment of unresectable HCC was reported in 2020, and this drug combination is now the standard treatment for unresectable HCC with preserved liver function.…”
Section: Introductionmentioning
confidence: 99%